THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON FINANCIAL PERFORMANCE: A LITERATURE REVIEW STUDY - Failasufa, Mila; Fuadah, Luk Luk (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
The purpose of this study is to systematically analyze previous research on the application of corporate social responsibility to financial performance. Using the Systematic Literature Review (SLR) approach, this study identifies, evaluates, and synthesizes findings from 38 scientific journals indexed by Scopus, Q1, Q2, Q3 and Sinta 2 to Sinta 3 for 5 years, from 2020 to 2024. The results of the review indicate that CSR can improve financial performance by increasing reputation, customer loyalty, and access to capital. However, in some cases, excessive CSR investment can be a financial burden for the company. Factors such as ownership structure, CSR regulations. Several studies have also found that the relationship between CSR and financial performance is not always linear, but can be U-shaped or inverted U-shaped